Managing Waste Throughout Lean-Green Perspective (Journal of University of Babylon for Engineering Sciences, 2017)
Managing waste has been known as a crucial need as it may reduce resource consumption, rigid regulations regarded to the environment and occupational health and safety. Lean and green management are two approaches of management that validate waste. Since performance measures are crucial to improve waste management as its  goals of  to promote the performance of organizations .In this research four primary KPIs have been employed that are significant to lean-green management; operational, environmental, economic and social performance factors, subdivided further into sixteen as (Value stream mapping, life cycle assessment,---etc). Also in this research   determination and ranking of these performance measures and their influence on waste minimization is conducted. Interpretive Structural Modeling (ISM) methodology is applied to the classification of Key Performance Indicators (KPIs) according to the priority of their importance and the correlation between them and their impact to waste minimization. Cronbach’s Alpha coefficient is employed  to assess the reliability of performance measures to minimize waste, and increase customer  satisfaction.  Results showed that Al-Kufa Cement plant has bad overall performance toward lean green waste management perspective. The highest individual score is for operational performance (6.6) rated as medium. But  the lowest individual score is for economic performance [very bad (2.0)].